ToDIGRA Diversity Workshop Special Issue: Introduction - Beavers, Sian; Jayemanne, Darshana (Transactions of the Digital Games Research Association, 2018)
The inaugural DiGRA DiversityWorkshop, “Gaming the System”, was held at The University of Melbourne on 2nd July 2017; we thank and acknowledge the Wurundjeri people as Traditional Custodians of this land. The Workshop was an initiative of the Diversity Working Group that first met in 2015. The event drew together five formal papers (four of which have proceeded to peer review and appear in this special issue) followed by a general discussion. The aim of the Workshop was to critically interrogate what it would mean for Game Studies to be diverse, and to invite presentations that could expand our ideas about diversity. This included questioning whether ‘diversity’ is an unalloyed good, the nature of the non-diverse ‘norm’ from which it putatively offers a departure, and the function of diversity as a discourse operative within the contemporary academy.